Implementation Of Team Game Tournament Model To Improve Student Learning Results On Fraction - Tarusu, D T (Journal of Educational Method and Technology, 2019)
This study aims to improve the learning outcomes of mathematics in elementary school, especially in fraction material by applying the Team Game Tournament (TGT) learning model. This study uses the Classroom Action Research (CAR) method which refers to the opinion of Kemmis and Mc Taggart with 4 stages: planning, action, observation, and reflection. The subjects of this study were the fifth grade students of GMIM I Tomohon Elementary School totaling 15 students. This research was conducted in two cycles. The results obtained in the first cycle reached 46.67%, while in the second cycle it reached 86.67%. Thus it can be concluded that by applying the Team Game Tournament (TGT) model can improve student learning outcomes, especially in fraction addition and subtraction count operations in class V of GMIM I Tomohon Elementary SchoolÂ Keywords: Team Game Tournament Model, Learning Outcomes, Fractions